Pakistan’daki dini cemaatler ve din eğitimi (mevdudi cemaati örneği) - Jabeen, Farkhunda (My University, 2022)
Pakistan, İslamiyet'in yayıldığı ilk yerlerden biridir. İslamiyet’in hakimiyeti uzun yıllar burada egemenliğini sürdürdüğünden, ilk zamanlarda İslamiyet azınlıkta ve dış öge gibi dururken zamanla yerli halkın dikkatini çekerek çoğunluğun benimsediği bir din haline gelmiştir. İslamiyet'le birlikte medreselerin kurulumu ve artışı sağlanmıştır. Pakistan'daki dini eğitimin en büyük sorunu müfredatın güncelleştirilme ve eğitime kazandırılan birey sayılarının düşük olma sorunudur. Özellikle devletin dini İslam olduktan sonra, milletin önderlerinden olan Mevdudi'nin kurduğu cemaat din eğtimine önemli katkılarda bulunmuştur. Tezimizde Pakistan'da yer alan cemaatlerin iç yapısı ve eğitim sistemi incelenerek Mevdudi cemaatinin özellikleri ve din eğitimine katkılarına değinilmiştir. Tezimiz Pakistan'daki cemaat algısına derinlemesine bakış açısı sunarak, din eğitimindeki eksiklikleri ve değişimleri ele alıp konu hakkında alana bilgi zenginliği sunarak katkıda bulunacaktır.

Pakistan is one of the first places where Islam spread. Since the dominance of Islam has been dominant here for many years, in the early days, Islam stood as an external element in the minority and over time attracted the attention of local people and became a religion adopted by the majority. With the advent of Islam, the establishment and increase of madrasas was achieved. The biggest problem of religious education in Pakistan is the problem of updating the curriculum and the low number of individuals enrolled in education. In particular, after the religion of the state became Islam, the community founded by Modudi, one of the leaders of the nation, made an important contribution to the education of religion. In our thesis, the internal structure and education system of the communities in Pakistan were examined and the characteristics of the Modudi community and their contribution to religious education were discussed. Our thesis will contribute by providing an in-depth perspective on the perception of the community in Pakistan, addressing the shortcomings and changes in religious education and providing a wealth of information on the subject to the field.
Religious communities and religious education in Pakistan (sample of Modudi community)
Keywords: Cemaat; Din eğitimi; Islam and politics; İslam ve politika; Mevdudi; Mevdudi Cemaati; Pakistan; Pakistan Jamaat; Religious education; Religious Education Mevdudi